Impedance spectroscopy analysis of the diffuse phase transition in lead-free (Ba0, 85Ca0, 15)(Zr0.1Ti0.9)O3 ceramic elaborated by sol-gel method. (March 2019) - Belkhadir, S.; Ben Moumen, S.; Asbani, B.; Amjoud, M.; Mezzane, D.; Luk'yanchuk, Igor A.; Choukri, E.; Hajji, L.; Gagou, Y.; El Marssi, M.
Abstract: We investigate the lead free ferroelectric perovskite ceramic, (Ba0.85 Ca0.15 )(Zr0.1 Ti0.9 )O3 (BCZT), prepared by sol-gel method. The as-synthesized precursor powder is calcined at 1000 °C for 4 h in order to obtain single-phase perovskite structure. X-ray diffraction (XRD) analysis at room temperature shows the formation of single-phase compound with a tetragonal structure refined in P 4mm space group. The dielectric measurements in a frequency range of [100 Hz-1 MHz] and in a temperature range [35–400 °C] in the ceramic sintered at 1350 °C for 2 h, reveal a high maximum dielectric constant ∼5200 (100 Hz) at 107 °C, which is associated with ferroelectric paraelectric phase transition. The sol-gel method has displayed a very important advantages comparing to the conventional solid-state method. Special emphasis was done to characterize diffuse phase transition (DPT) that occurs close to ∼107 °C. We have shown that the real part of the permittivity close to DPT is well described by Santos–Eiras phenomenological model. Impedance spectroscopy analysis over the frequency range of 100 Hz to 1 MHz illustrated mainly bulk contribution up to 300 °C while grain and grain-boundary effects were present above 300 °C using the impedance spectroscopy technique. Highlights: The XRD study showed a pure perovskite structure without impurities with tetragonal symmetry refined to P4mm space group. The sol-gel method has displayed a very important advantages comparing to the conventional solid-state method. The real part of the permittivity close to DPT is well described by Santos–Eiras phenomenological model.